Linking Business Ownership and Perceived Administrative Complexity: An Empirical Analysis of 18 OECD Countries - André J. van Stel; Viktor Stunnenberg (Max Planck Institute for Research into Economic Systems, 2004)
Administrative burdens are known to be a major business constraint for incumbent SMEs in modern economies. Far less is known about the influence of these burdens on the startup of new firms. The current paper examines to what extent perceived administrative complexity related to starting a new business influences the number of business owners across 18 OECD countries. We test this relationship combining data on business ownership from EIM's COMPENDIA data base and data on perceived administrative complexity from the Eurobarometer public opinion surveys coordinated by the European Commission. Our regression model enables to explicitly control for the influence of unemployment on the level of business ownership ('refugee effect'). We also control for risk tolerance and access to finance. Our results suggest that perceived administrative complexity has a negative impact on the level of business ownership. However, the effect is not immediate but rather seems to emerge in the long run.
Keywords: M13; L50; O57; 330; business ownership; administrative burdens; unemployment; Unternehmer; Selbstständige; Eigentümerstruktur; Bürokratie; Folgekosten; Schätzung; OECD-Staaten